Utilization of Sugarcane Bagasse Ash in Portland Composite Cement: Effects on Mortar Compressive Strength - Alif Nur Laili Rachmah; Binti Ruliana; Sabrianah Badaruddin; Geraldi Rahanra; Ratri Sekaringgalih; Achmad Qodim Syafaatullah (Journal of Fundamentals and Applications of Chemical Engineering, 2025)
Sugarcane Bagasse Ash (SBA) is an agricultural biomass waste with a high content of reactive silica, making it a promising candidate as a pozzolanic additive in mortar based on Portland Composite Cement (PCC). This study investigates the influence of SBA incorporation on the compressive strength of mortar by substituting cement at levels of 5%, 10%, and 15% by weight. The SBA was prepared through calcination at 650 °C and further treated with 2N hydrochloric acid (HCl) to enhance its amorphous silica composition. Compressive strength tests were conducted at 3, 7, and 28 days of curing. Results indicate that the 5% SBA mixture provided the highest compressive strength, reaching 303–301 kg/cm² on day 28, and met the Indonesian National Standard (SNI 15-7064-2014) for structural applications. The Pozzolanic Activity Index (PAI) of 76% further confirmed SBA’s reactivity as a pozzolan under ASTM C618-99 criteria. Beyond mechanical performance, SBA utilization reduces clinker consumption and CO₂ emissions, promoting sustainability in cement production. Additionally, the formation of additional calcium silicate hydrate (C–S–H) gel improves the mortar’s microstructure. In conclusion, SBA is a feasible, locally available, and environmentally friendly alternative for enhancing the performance and sustainability of cement-based building materials.